PERAN HUKUM TELEKOMUNIKASI TERHADAP IMPLIKASI KONVERGENSI TEKNOLOGI INFORMASI DAN KOMUNIKASI - Danrivanto Budhijanto (Jurnal Dinamika Hukum, 2014)
The implication of Information and Communication Technologies (ICT) convergence toward national legislation in the framework of ICT development requires understanding of basic principles in tec-hnology, industrial, and regulation aspects. The importance of establishing legal convergence con-cept is aimed at anticipating the implication of ICT convergence in regard to support Indonesian development in accordance with the role of technology in modern era especially for human life and its implication to their environment. This understanding will encourage the process of establishing legislation which governs all concerns which is closely relevant to regulated sectors or issues in such legislation particularly in telecommunications sector, in which such legislation becomes a regulation in accordance with the function of law. The legislation approach, regulation approach, and self-regulatory approach might be used to anticipate the ICT convergence implications. Keywords: convergence, regulation, telecommunications